Improving Skills for Peer Feedback on Spoken Content Using an Asynchronous Learning Analytics App (International Conference on Computers in Education, 2020)
Peer feedback can have a powerful effect on language learning outcomes. However, training students to successfully provide peer feedback and the subsequent evaluation of that feedback can be challenging. The first author’s Ph.D. dissertation research will investigate how to improve that training process within the context of English as a foreign language education. First, this paper will describe the preliminary research questions and the motivations underlying these questions. Then, it will describe the design and development of the alpha version of a web app that supports training students to provide peer feedback on spoken content. This app will also be able to act as a platform which supports learning analytics (LA) research. Finally, this paper will lay out the proposed research methodology for moving forward.